Character Education Management Through Religious Habituation in Junior High School - Faiq Akmaluddin Hafidzh; R. Madhakomala (Ravine Publisher, 2024)
Character is a form of behavior of a person that is related to actions, words, feelings, attitudes, thoughts, environment, social, self, and relationship to God based on current regulations. Religious character is the behavior shown to a person to carry out what is commanded in Islam and stay away from all forms of His prohibitions. In another context, Indonesia is a Pancasila country, where the first principle explains